Dynamics of International Regulatory and Investigation Cooperation in Handling Crypto-Related Economic Crimes - Isyfa Fuhrotun Nadhifah; Agwanwo Destiny Eze (Generate Digital Publishing, 2026)
Objective: This study aims to evaluate the effectiveness of regulatory models across selected jurisdictions such as the United States, Brazil, China, Thailand, Indonesia, and the European Union and to analyze emerging trends in crypto-related economic crime, particularly in relation to implementation gaps in FATF Recommendation 15, namely the Travel Rule, and the resulting cross-jurisdictional regulatory arbitrage dynamics.Research Design & Methods: This study uses a comparative qualitative approach through document analysis and cross-country case studies. Secondary data comes from FATF, Interpol, UNODC, Chainalysis reports, national regulations, and academic literature, which are analyzed using thematic content analysis and comparative regulatory analysis. Findings: Research findings indicate that regulatory fragmentation and gaps in the implementation of FATF standards create regulatory arbitrage loopholes that are exploited by crypto criminals. Crypto crime in the 2024-2025 period is becoming more professionalized, marked by the dominance of stablecoins, the involvement of state actors, and low asset recovery rates. Network-based international investigative cooperation, has proven to be more adaptive than unilateral repressive approaches. Implications: There is a need for harmonization of cross-border AML policies, acceleration of Travel Rule implementation, and strengthening of informal investigative cooperation mechanisms and public private partnerships with VASPs to improve the effectiveness of asset tracing and recovery. Contribution & Value Added: This study enriches the literature on digital economic crime by linking regulatory arbitrage and FATF networked governance, and provides the latest empirical evidence for the formulation of adaptive AML policies in the era of decentralized finance.